Integration of Traditional Strategies And Technology in Teaching Academic Vocabulary to Non-Native English Speakers - Astuti, Dwi; Subarjo, Subarjo; Ramadani, Fitra; Guswenda, Nuan Ifga (Ethical Lingua: Journal of Language Teaching and Literature, 2026)
This research explores how English teachers integrate traditional strategies with technological tools in teaching academic vocabulary to non-native English learners. Using a qualitative phenomenological design, data were collected through interviews and classroom observations with two teachers from different educational contexts in Indonesia. The findings reveal that memorization serves as a foundation for discipline and retention, while contextual practices, games, and multimedia resources such as short videos and digital worksheets enhance engagement, confidence, and performance. Both teachers demonstrate that balancing conventional rigor with modern innovation fosters meaningful vocabulary mastery and supports broader academic achievement. This research contributes to the literature by highlighting the synergy between traditional and technological approaches, offering insights into effective pedagogical practices that can be adapted across diverse learning environments.